Training and competitive activity of biathletes at the stage of sports perfection with using air rifles (on the example of the Omsk region) - Romanova, Ya. S.; Zagursky, N. S. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article analyzes the current state and prospects of development of pneumatic biathlon on the example of the Omsk region. The contradictions in the implementation of the program for the development of pneumatic biathlon are shown and experimental format for conducting the competitions using gas bottles and spring-piston air rifles is proposed. The comparative analysis of the technical and tactical actions of biathletes at firing ranges when firing from different types of air rifles is given. The analysis of design features of various air rifles for biathlon competitions is presented.